Super-anti-freezing, tough and adhesive titanium carbide and L-ornithine-enhanced hydrogels - Li, Zhangkang; LeBlanc, Jamie; Kumar, Hitendra; Zhang, Hongguang; Yang, Weijun; He, Xiao; Lu, Qingye; Van Humbeck, Jeffrey; Kim, Keekyoung; Hu, Jinguang (Journal of Bioresources and Bioproducts, 2023)
Hydrogels are highly porous three-dimensional crosslinked polymer networks consisting of hydrophilic polymers, employed most practically in medicine and industry, often as biosensors. Simple hydrogels suffer limitations in their mechanical properties, such as tensile and compression, and freeze at sub-zero temperatures, which compromise their ability as useful biosensors. In this study, the incorporation of L-ornithine-based zwitterionic monomer (OZM), titanium carbide (MXene), and glycerol within polyacrylamide hydrogels was used to prepare a novel polyacrylamide/polyL-ornithine-based zwitterion/MXene (PAM/Porn/MXene) hydrogel to improve the mechanical, adhesion, and anti-freezing properties of pure polyacrylamide hydrogels. This study also analyzed the mechanical strength (tensile and compression), adhesion, and anti-freezing properties of a novel PAM/Porn/MXene hydrogel at 1%, 4%, and 10% MXene concentrations to establish to what extent the conductive MXene material enhanced these properties and concluded that the tensile and compressive properties improved linearly with the increase in the concentrations of MXene, adhesion decreased with the increased MXene concentrations, and synergistic interaction between MXene and OZM significantly improved the anti-freezing properties up to –80 °C.